Pengembangan Model Pembelajaran IPA Terintegrasi Nilai Karakter di Sekolah Dasar - Ismail . (Paedagogik, 2013)
The character of the nation is currently experiencing a servere fragility. Various people rate as result of the imbalance of purpose in educational practice in schools. The purpose of learning is not oriented of cultivation of characters, but more cognitively oriented. This study aimed to develop science learning model integrated with character value (Model PIN-Karakter) in elementary school are valid, practical, effective and attractive to conceice a character value and improve science learning outcomes.